Dysregulation of the NLRP3 Inflammasome and Promotion of Disease by IL-1β in a Murine Model of Sandhoff Disease - Nick Platt; Dawn Shepherd; David A. Smith; Claire Smith; Kerri-Lee Wallom; Raashid Luqmani; Grant C. Churchill; Antony Galione; Frances M. Platt (Cells)
Sandhoff disease (SD) is a progressive neurodegenerative lysosomal storage disorder characterized by GM2 ganglioside accumulation as a result of mutations in the HEXB gene, which encodes the β-subunit of the enzyme β-hexosaminidase. Lysosomal storage of GM2 triggers inflammation in the CNS and periphery. The NLRP3 inflammasome is an important coordinator of pro-inflammatory responses, and we have investigated its regulation in murine SD. The NLRP3 inflammasome requires two signals, lipopolysaccharide (LPS) and ATP, to prime and activate the complex, respectively, leading to IL-1β secretion. Peritoneal, but not bone-marrow-derived, macrophages from symptomatic SD mice, but not those from pre-symptomatic animals, secrete the cytokine following priming with LPS with no requirement for activation with ATP, suggesting that such NLRP3 deregulation is related to the extent of glycosphingolipid storage. Dysregulated production of IL-1β was dependent upon caspase activity but not cathepsin B. We investigated the role of IL-1β in SD pathology using two approaches: the creation of hexb−/−Il1r1−/− double knockout mice or by treating hexb−/− animals with anakinra, a recombinant form of the IL-1 receptor antagonist, IL-1Ra. Both resulted in modest but significant extensions in lifespan and improvement of neurological function. These data demonstrate that IL-1β actively participates in the disease process and provides proof-of-principle that blockade of the pro-inflammatory cytokine IL-1β may provide benefits to patients.